Analysis bibliometrics study reasoning mathematical in mathematics education: trends, structures, and implications for elementary school education - Yunni Arnidha; Agus Suyatna; Sugeng Sutiarso (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
Mathematical reasoning is a fundamental competency in mathematics education that supports students' logical, critical, and systematic thinking skills. Along with technological advancements and the growing demands of twenty-first-century learning, research on mathematical reasoning has expanded significantly and become increasingly multidisciplinary. This study employed a bibliometric analysis to map the global development of research on mathematical reasoning in mathematics education. Data were retrieved from the Scopus database using the keywords